An investigation of ethical culture in educational organizations - Karakose, Turgut; Kocabas, Ibrahim (Academic Journals, 2009)
The main objective of the research is to analyse the opinions of teachers in state high schools about organizational ethics in terms of various variables and to develop suggestions in the light of findings. The study has a descriptive quality in evaluating the teachers' opinions and uses the likert type scale developed by researchers so as to determine the opinions of the participants. The population of the study is composed of teachers working at government high schools in the city of Kutahya, a province located in the western part of Turkey. At the end of this research, it was determined that; the opinions of teachers regarding the organizational ethics vary significantly according to years of experience, gender and branch by the participants. In addition, female teachers think more positively than male ones about the ethical culture at school. On the other hand, while teachers with high seniority think more negatively about the ethical culture at school, other teachers were more indecisive about the matter. Collectively, science teachers, compared to teachers of social sciences, consider their schools more reputable in terms of ethics.
Keywords: Organizational ethics; principal; school; ethical culture; teacher